2014
DOI: 10.3141/2421-11
|View full text |Cite
|
Sign up to set email alerts
|

Volume Delay Functions Based on Stochastic Capacity

Abstract: The standard highway assignment problem is solved by using a volume delay function (VDF). The primary link impedance is travel time, which increases with an increasing degree of saturation. VDFs contain link-specific input parameters, such as capacity and free-flow speed, as well as coefficients depending on VDF type. The coefficients either are taken from guidelines or are estimated from site-specific data. Because free-flow speed can be measured directly, mean values usually are used for particular links or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…It is a polynomial function, whose coefficients need to be calibrated using empirical data ( 4 ). Generally, 0.15 and 4 are used for α and β, respectively ( 2 ). Simple mathematical form, fewer and easily field-observable inputs, and reasonable performance are some of the reasons for its popular acceptance ( 5 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a polynomial function, whose coefficients need to be calibrated using empirical data ( 4 ). Generally, 0.15 and 4 are used for α and β, respectively ( 2 ). Simple mathematical form, fewer and easily field-observable inputs, and reasonable performance are some of the reasons for its popular acceptance ( 5 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The empirical travel time is obtained as explained in the previous section. The BPR travel time values are calculated using the BPR function (Equation 1) with the assumed values of α = 0.15, β = 4, and free-flow velocity, uf = 40 km/h, which is the speed limit on the study corridor ( 2 ). Similarly, the intersection delay values are obtained from the HCM delay model (Equation 2).…”
Section: Validation Of Link Cost Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past studies have identified the need to inform these functions with empirical and context-specific data (Rose et al, 1989;Spiess, 1990), but also recognize the difficulty and cost associated with collecting such empirical data as being prohibitive (Rose et al, 1989). There have been studies that incorporate different forms of field sensor data for such calibration (Mtoi and Moses, 2014;Neuhold and Fellendorf, 2014;Kucharski and Drabicki, 2017). Nevertheless, the data used in these studies have been generated specifically for that application and requires specific hardware and software for use.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Focusing on auto travelers, the internal and external costs are defined as follows: Travel time can be divided into congested and uncongested components, in which congested time implies the external cost imposed on others from the point-of-view of travelers, as additional vehicles on the roadways result in incremental delay borne by others (e.g., following travelers in the stream of traffic) (Levinson and Gillen 1998). Delay is highly related to traffic flow, which increases significantly as traffic flow reaches and exceeds capacity (Neuhold and Fellendorf 2014). Considering link properties, traffic and capacity, the marginal cost of travel time represents the external time cost.…”
Section: Fca Analysis Frameworkmentioning
confidence: 99%